1989
DOI: 10.1099/00221287-135-12-3459
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Mutant of Trichoderma reesei Showing Reduced Levels of Extracellular  -Glucosidase

Abstract: A mutant (D6-1 3 ) of Trichoderma reesei that produced low levels of extracellular /?-glucosidase was physiologically and biochemically characterized. The mutant was unable to grow and produced very little cellulase activity on Solka-Floc, Avicel, micro-crystalline cellulose and acidswollen cellulose. Whereas growth was nearly normal on cellobiose, lactose and glucose, cellulase production was slightly decreased on cellobiose and lactose. The mutant produced nearly normal levels of FPA (filter-paper activity) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The study found that although the absence of bgl1 caused delayed induction of cellulase enzymes, it had no effect on growth or mRNA production abilities of the cell. However, other gene disruption studies on β-glucosidase genes produced different results (Mishra et al, 1989;Strauss and Kubicek, 1990), leading us to believe that specific functional analysis of this gene in L. maculans is required.…”
Section: Beta-glucosidase (Lema_g0684601)mentioning
confidence: 99%
“…The study found that although the absence of bgl1 caused delayed induction of cellulase enzymes, it had no effect on growth or mRNA production abilities of the cell. However, other gene disruption studies on β-glucosidase genes produced different results (Mishra et al, 1989;Strauss and Kubicek, 1990), leading us to believe that specific functional analysis of this gene in L. maculans is required.…”
Section: Beta-glucosidase (Lema_g0684601)mentioning
confidence: 99%